Evaluación de los Niveles de Progesterona en receptoras Holstein Friesian Transferidas en relación al Indice de Gestación. - Durán Martínez, Jacqueline Paulina (2018)
In the change of bovine embryos, several stages are recognized that begin with the donor female and ends with the receptor cows. The studies focus on the recipient and its influence on the percentage of pregnancy, relating it to race, age, health status, nutritional and productive level. However, the functional corpus luteum (C.L.) depends on the luteotrophic and antiluteolytic signals of the embryos. The objective of the present study was to evaluate the gestation rate in recipient embryos transferred and their relationship with plasma progesterone levels. For the experiment, 12 recipients of the Holstein Friesian breed were used, which were synchronized using an IATF protocol; the recipients were transfered fresh embryos grade 1 morulas on day 7 after heat detection. Whole blood samples were collected to determine the plasma levels of progesterone (P4) at day 7, 14 and 21 post transfer, and the diagnosis of pregnancy was made on day 25 and 35 with Aloka SSD5 ultrasound. For the statistical analysis, the Student's t test was used. . It was determined that the gestation rate in recipients transferred embryos on day 7 is directly related to plasma progesterone levels and embryo quality. Plasma progesterone levels in embryo recipients at day 7, 14 and 21 determined mean values that correspond to embryonic survival in the uterine lumen; in addition, the gestation rate of the recipients showed variability between day 25 and 35, since a high percentage of embryonic death was determined. Therefore it is concluded that plasma progesterone concentration levels directly affect the gestation index, and the progesterone concentration (P4) necessary for an embryo to survive during the third week post-implant is not yet defined